1999
DOI: 10.1063/1.124343
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of bright and dark microwave magnetic envelope solitons in a resonant ring

Abstract: The excitation of both bright and dark microwave magnetic envelope solitons has been realized for one and the same resonant ring containing a yttrium–iron–garnet film magnetostatic wave (MSW) delay line. The resonant ring modifies the MSW character to produce a series of frequency intervals with alternating regions of positive and negative dispersion. These alternating regions support bright and dark soliton production, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…2 and 3 mirror and extend previous results for single peaked solitons. [3][4][5][6] These studies have shown that, when there is appropriate compensation between the dispersion and the nonlinear response, one can form a robust and non-dispersive bright MME soliton with a CP profile across the peak. Constant phase, therefore, provides a simple unambiguous criterion for bright MME soliton formation.…”
Section: A Spatial Evolutionmentioning
confidence: 98%
See 1 more Smart Citation
“…2 and 3 mirror and extend previous results for single peaked solitons. [3][4][5][6] These studies have shown that, when there is appropriate compensation between the dispersion and the nonlinear response, one can form a robust and non-dispersive bright MME soliton with a CP profile across the peak. Constant phase, therefore, provides a simple unambiguous criterion for bright MME soliton formation.…”
Section: A Spatial Evolutionmentioning
confidence: 98%
“…More specifically, Ref. 3 and later papers [4][5][6] show that single MME soliton pulses have a constant phase (CP) profile across the center part of the pulse. It is expected that multipeaked soliton (MPS) entities should also have peaks with a CP character.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the possibility of dissipative soliton train self-generation in the MW feedback oscillators with the ferromagnetic film was demonstrated [3]- [10]. Such MW pulse trains are formed because of synchronization and frequency filtration of spectral components of a complex-modulated MW signal.…”
Section: Introductionmentioning
confidence: 99%
“…Using (11)(12)(13)(14)(15) for given values of the excitation frequency ω = ω 0 (determined by the frequency of the external microwave signal, the bias magnetic field H, and the saturation magnetization of the material M 0 ), it is easy to calculate the dependence of the direction of the group velocity on the direction of the phase velocity in the excited wave beam θ = f (ϕ). This dependence, calculated for the parameters of the experiment described below, is presented in Fig.…”
Section: Basics Of Nonlinear Spin-wave Phenomena In Magnetic Filmsmentioning
confidence: 99%
“…These processes can be used to design a new generation of nonlinear spinwave signal-processing devices that are magnetically tunable in a wide frequency range and could be easily integrated into modern planar technologies. In particular, such devices include frequency-selective limiters [7]; signal-to-noise enhancers [7,8,9]; nonresonant and resonant convolvers [10,11]; recently developed active ring soliton generators [12]; and active delay lines for pulse amplification, phase conjugation, and pulse shaping [13,14,15].…”
Section: Introductionmentioning
confidence: 99%